Effectiveness of Law Enforcement Against Alcoholic Beverage Sales Locations in Kendari City Based on Minister of Trade Regulation No. 20 of 2014: Efektifitas Penegakan Hukum Terhadap Tempat Penjualan Minuman Beralkohol Di Kota Kendari Berdasarkan Peraturan Menteri Perdagangan No. 20 Tahun 2014 - al azis (QAIMUDDIN: Journal of Constitutional Law Review, 2025)
The circulation of alcoholic beverages is a complex issue in Kendari, Southeast Sulawesi, involving concerns for public health and safety. Although Minister of Trade Regulation No. 20 of 2014 regulates the supervision and control of alcoholic beverage circulation, its implementation at the local level remains suboptimal. This study aims to evaluate the effectiveness of law enforcement against alcoholic beverage vendors in Kendari based on the applicable regulations. The research employs a normative, juridical-empirical approach. Primary data was obtained through a review of Minister of Trade Regulation No. 20 of 2014, while secondary data was collected through interviews with law enforcement officials and field observations. The data analysis technique employed is qualitative descriptive analysis, which aims to identify practices, obstacles, and opportunities for policy improvement. The findings suggest that law enforcement efforts aimed at curbing the sale of alcoholic beverages in Kendari have been ineffective. The study reveals a lack of coordination among law enforcement agencies, low public legal awareness, and the absence of synchronization between Minister of Trade Regulation No. 20 of 2014, the Omnibus Law on Job Creation, and related risk-based licensing regulations. The gap between national regulations and field practices is further widened by the lack of regional regulations specifically governing the supervision of alcoholic beverages. This study suggests the need for stricter regional regulations, enhanced capacity among law enforcement personnel, and stronger public education to improve the effectiveness of monitoring the circulation of alcoholic beverages in Kendari.